Excess flesh: a study on the universal commodification and consumption of the colored body - Holmes, Jasmine Nicole, author; Lehene, Marius, advisor; Souza, Caridad, committee member; Dineen, Mark, committee member; Plastini, Johnny, committee member (Colorado State University. Libraries, 2020)
First, the breakdown of hegemony and the creation of "race" must be explored before moving onto the branching facets of commodified colored figures: Entertainment, Labor, Sexuality. Western societies' basic understanding of race is laced with phenotypical notions. The term itself is entwined within every societal construct that exists within the contemporary world. In order to completely discuss my artistic practice and the pieces that have developed throughout my time within this program, we must study these compartments of racial discrimation and overall consumption of the Black form.
Keywords: eugenics; race theory; art; socio-political; race disparities